Students' Decision-Making in Solving Mathematical Word Problems Based on Adversity Quotient - Savitri, Ellita Destriani; Natalliasari, Ike; Hermanto, Redi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aims to describe students’ decision-making processes in solving mathematical word problems based on their Adversity Quotient (AQ). A qualitative research method was employed. Data were collected through AQ questionnaires, decision-making tests, and interviews. The data analysis techniques included data reduction, data presentation, verification, and conclusion drawing. The findings revealed the presence of 2 climber-type students, 5 students transitioning from camper to climber, 16 camper-type students, and 4 students transitioning from quitter to camper; no students were identified as quitters. The results show that climber-type rational students fulfilled all indicators of decision-making. Rational students transitioning from camper to climber fulfilled all indicators except for recalling the relationship between the problem, known information, and the decision made. Heuristic students in this category were unable to present or recall that relationship. Camper-type students with intuitive and rational decision-making styles were able to identify problems and goals, find alternative solutions, solve the problems, evaluate the alternatives, and make decisions. Students transitioning from camper to quitter with an intuitive style could identify problems, find alternative solutions, solve the problems, and make decisions. Meanwhile, those with a rational style could only find alternative solutions, solve the problems, and make decisions.